PENGARUH AGRESIVITAS SISWA TERHADAP PRESTASI BELAJAR SISWA MADRASAH IBTIDAIYAH AL-AMIEN TEGAL PRENDUAN SUMENEP - Ahmadi Ahmadi; Harisah Harisah (Reflektika, 2019)
This study wanted to find out whether there was an influence of student aggressiveness on student achievement in MI. Al-Amien Tegal Prenduan Sumenep Madura for the 2016-2017 academic year, and wanted to find out how much influence student aggressiveness had on MI student achievement. Al-Amien Tegal Prenduan Sumenep Madura academic year 2016-2017. This study uses quantitative research. The subjects of this study were students with a population of 249 students. But only took a sample of 50 students with a presentation of 20%. While the data collection techniques used questionnaires, observation and documentation, as well as data analysis using Linear Regression with the help of IBM SPSS Statistics v 22 for Windows Software. From the results of data analysis using Linear Regression with the help of IBM SPSS Statistics v 22 for Windows software, the R squere value or Coefficient of Determination (KD) is 0.301 which implies that the effect of the independent variable on changes in the dependent variable is 0.301 (0.301 X 100% = 30.1%). Based on the results of the analysis, it turns out that the significant level or linearity of the regression is 0.000 <0.05. Thus it can be concluded that the working hypothesis (Hi) which states that there is an effect of student aggressiveness on student achievement MI. Al-Amien Tegal Prenduan Sumenep Madura Academic Year 2016-2017 can be accepted. Meanwhile, the null hypothesis (Ho) states that there is no effect of student aggressiveness on MI student achievement. Al-Amien Tegal Prenduan Sumenep Madura Academic Year 2016-2017 may be rejected.